2017
DOI: 10.3389/fpls.2017.01506
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Pathways Involved in Carbon Dioxide Enhanced Heat Tolerance in Bermudagrass

Abstract: Global climate changes involve elevated temperature and CO2 concentration, imposing significant impact on plant growth of various plant species. Elevated temperature exacerbates heat damages, but elevated CO2 has positive effects on promoting plant growth and heat tolerance. The objective of this study was to identify metabolic pathways affected by elevated CO2 conferring the improvement of heat tolerance in a C4 perennial grass species, bermudagrass (Cynodon dactylon Pers.). Plants were planted under either a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 69 publications
(106 reference statements)
0
15
0
Order By: Relevance
“…With the significant decrease in MDH and succinate dehydrogenase and increases in aspartic acid, the contents of threonine, isoleucine, lysine, alanine, valine and serine were elevated with exogenous GABA application at low temperature. It was reported that the levels of alanine, valine and serine were affected by the stimulation of elevated endogenous GABA under abiotic stresses: Bermuda grass under heat stress [65] and tobacco under salt [66]. The GABA shunt was considered to be a part of the TCA cycle during respiration [6769], which is also important in primary carbon and nitrogen metabolism [70].…”
Section: Discussionmentioning
confidence: 99%
“…With the significant decrease in MDH and succinate dehydrogenase and increases in aspartic acid, the contents of threonine, isoleucine, lysine, alanine, valine and serine were elevated with exogenous GABA application at low temperature. It was reported that the levels of alanine, valine and serine were affected by the stimulation of elevated endogenous GABA under abiotic stresses: Bermuda grass under heat stress [65] and tobacco under salt [66]. The GABA shunt was considered to be a part of the TCA cycle during respiration [6769], which is also important in primary carbon and nitrogen metabolism [70].…”
Section: Discussionmentioning
confidence: 99%
“…Leaf membrane stability was estimated by measuring EL following the procedure described in Martin et al (1987). The net photosynthetic rate (Pn) of the third fully expanded leaf of the plant at 30 DAE was determined by measuring the CO 2 uptake rate with an infrared gas analyzer (Li-6400, LI-COR, Inc., Lincoln, NE, USA) following the procedure described in Yu et al ( 2017b). For Pn measurements, six to eight leaves were enclosed in the leaf chamber (LI-COR 6400-11, 2 cm 9 6 cm aperture) suitable for narrow-bladed leaves that enclosed a 6-cm long section of a leaf with the gas exchange analyzer with the light intensity of 600 µmol photon m À2 sec À1 .…”
Section: Analysis Of Gene Expression By Qrt-pcrmentioning
confidence: 99%
“…The present study revealed a significant increase in shoot and root length in chickpea plants of both cultivars under elevated CO 2 concentrations. This could be attributed to enhanced vigor as the initial effect of elevated CO 2 concentrations in plants as evidenced by a number of previous studies ( Yu et al. 2017 ).…”
Section: Discussionmentioning
confidence: 63%
“…Moreover, these reports were not coherent studies that included both physiological and molecular alterations. A number of metabolic and proteomic studies have recently shown the alteration in various metabolic processes or pathways, such as photosynthetic carbon fixation, respiratory metabolism, cellular growth and stress defense under elevated CO 2 ( Yu et al. 2017 ).…”
Section: Introductionmentioning
confidence: 99%